2020
DOI: 10.1212/wnl.0000000000008747
|View full text |Cite|
|
Sign up to set email alerts
|

Long‐term follow‐up, quality of life, and survival of patients with Lambert‐Eaton myasthenic syndrome

Abstract: ObjectiveTo study survival and to characterize long-term functional impairments and health-related quality of life (HRQOL) of patients with Lambert-Eaton myasthenic syndrome (LEMS). MethodsIn this observational study, survival of patients with LEMS, separately for nontumor (NT) and small cell lung cancer (SCLC), was compared to that of the Dutch general population and patients with SCLC. Disease course in patients with LEMS was recorded retrospectively. Several scales for functional impairments and health-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 38 publications
(54 reference statements)
1
31
0
Order By: Relevance
“…In patients with NT-LEMS, life expectancy appears comparable to that of the general population [112]. Overall, functional impairment tends to be more severe in patients with paraneoplastic LEMS, although a recent study showed that the health-related quality of life does not differ significantly between patients with SCLC-and NT-LEMS [112]. A follow-up study on 47 patients with LEMS showed that 88% had an improvement of muscle strength whereas a sustained clinical remission was achieved in 43%.…”
Section: Treatment and Prognosismentioning
confidence: 88%
See 2 more Smart Citations
“…In patients with NT-LEMS, life expectancy appears comparable to that of the general population [112]. Overall, functional impairment tends to be more severe in patients with paraneoplastic LEMS, although a recent study showed that the health-related quality of life does not differ significantly between patients with SCLC-and NT-LEMS [112]. A follow-up study on 47 patients with LEMS showed that 88% had an improvement of muscle strength whereas a sustained clinical remission was achieved in 43%.…”
Section: Treatment and Prognosismentioning
confidence: 88%
“…Given the rarity of LEMS in association with tumors other than SCLC, there are no data on the prognosis of this group of paraneoplastic patients. In patients with NT-LEMS, life expectancy appears comparable to that of the general population [112]. Overall, functional impairment tends to be more severe in patients with paraneoplastic LEMS, although a recent study showed that the health-related quality of life does not differ significantly between patients with SCLC-and NT-LEMS [112].…”
Section: Treatment and Prognosismentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, it is a promising method to restore antitumor immune responses for the treatment of SCLC through the inhibition of CTLA-4 and PD-1/PD-L1 pathways. Interestingly, some studies have reported that the presence of paraneoplastic syndromes, such as Lambert-Eaton syndrome, most commonly accompanied by SCLC, is associated with a better prognosis for SCLC [ 22 , 23 ]. Moreover, tumor tissue from SCLC patients with neurologic paraneoplastic syndromes presented with increased tumor infiltrating lymphocytes [ 24 ].…”
Section: Monotherapy and Combination Therapy For Immunotherapymentioning
confidence: 99%
“…Approximately 87% of all Dutch LEMS patients are registered in the database, when assuming a prevalence of 2.5 per million [7] . However, there are indications that the actual prevalence in the Netherlands is higher [19] . Two participants declined retrieval of medical information.…”
Section: Patients Characteristics and Demographicsmentioning
confidence: 99%